Analysis of the Most Relevant Factors for Routing in Internet of Space Things Networks - Eduardo Garcia-Loya; Alejandro Galaviz-Mosqueda; Salvador Villarreal-Reyes; Raúl Rivera-Rodríguez; José E. Lozano-Rizk; Roberto Conte-Galván (Applied Sciences, 2022)
The “Internet of Space Things” (IoST) is an emerging paradigm to provide Internet and data services around the globe. IoST networks can potentially support the deployment of services in underserved areas, such as monitoring inaccessible areas for early warning applications, open ocean and sea ice monitoring, and surveillance of remote ecosystems such as forests and jungles, among others. To enable the IoST paradigm, designing and developing appropriate routing protocols is crucial. This work presents a methodology based on 2k factorial statistical analysis and an in-house developed space simulator (available upon request) to identify the critical factors affecting the performance of routing protocols in “Internet of Space Things” scenarios. The analyzed factors consider reactive and proactive routing approaches, connectivity, and the freshness of routing information. The results provide essential lessons for the research community to design protocols that could adapt under different IoST scenarios. The 2k factorial analysis applied in the study of the routing protocols’ performance can be an effective tool for developing specialized routing protocols.